NEW APPROACHES IN THE STUDY OF MEDIA TEXTS - Shamaksudova Saodat Khidoyatovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the concept of media text, areas of their study, aspects of media linguistics and the study of media language. The methodological apparatus, internal structure and main sections of media linguistics are considered. As a result of the rapid development in recent years of the level of study of the media in world linguistics, it became known that the language of the media is studied on the basis of its many connections and functions. The research material was collected using Uzbek and foreign literature. The aim of the work is to show the need for an integrated approach to the study of media texts, which is the main object of research in media linguistics.